Tooth loss after active periodontal therapy. 2: tooth-related factors - Bernadette Pretzl (Blackwell Synergy)
Objective: To assess tooth-related factors contributing to tooth loss over a period of 10 years after completion of active periodontal therapy (APT). Material and Methods: All patients who had received APT by the same experienced periodontist, 10 years before beginning the research, were recruited until 100 patients were re-examined. Examinations included, at the patient level: test for interleukin-1 polymorphism, compliance to supportive periodontal therapy (SPT), mean plaque scores during SPT; at the tooth level: assessment of baseline bone loss (type, amount), tooth type, furcation status and abutment status. Logistic multilevel regression was performed for statistical analysis. Results: Hundred patients with 2301 teeth at the baseline (completion of APT) were retrospectively examined. One hundred fifty-five teeth were lost over 10 years after APT. Logistic multilevel regression identified high plaque scores, irregular attendance of SPT and age as patient-related factors significantly accounting for tooth loss. Tooth-related factors significantly contributing to tooth loss were baseline bone loss, furcation involvement and use as an abutment tooth. However, in patients with regular SPT, 93% of teeth with 60–80% bone loss at the baseline, survived 10 years. Conclusion: The following tooth-related risk factors for tooth loss were identified: baseline bone loss, furcation involvement, and use as an abutment tooth.